Electrophysiological Effects of Trace Amines on Mesencephalic Dopaminergic Neurons - Ledonne, Ada; Berretta, Nicola; Davoli, Alessandro; Ricciardo Rizzo, Giada; Bernardi, Giorgio; Mercuri, Nicola B. (Frontiers in Systems Neuroscience, 2011)
Trace amines (TAs) are a class of endogenous compounds strictly related to classic monoamine neurotransmitters with regard to their structure, metabolism and tissue distribution. Although the presence of TAs in mammalian brain has been recognized for decades, until recently they were considered to be by-products of amino acid metabolism or as ‘false’ neurotransmitters. The discovery in 2001 of a new family of G protein-coupled receptors (GPCRs), namely trace amines receptors, has re-ignited interest in TAs. In particular, two members of the family, trace amine receptor 1 (TA1) and trace amine receptor 2 (TA2), were shown to be highly sensitive to these endogenous compounds. Experimental evidence suggests that TAs modulate the activity of catecholaminergic neurons and that TA dysregulation may contribute to neuropsychiatric disorders, including schizophrenia, attention deficit hyperactivity disorder, depression and Parkinson’s disease, all of which are characterised by altered monoaminergic networks. Here we review recent data concerning the electrophysiological effects of TAs on the activity of mesencephalic dopaminergic neurons. In the context of recent data obtained with TA1 receptor knockout mice, we also discuss the mechanisms by which the activation of these receptors modulates the activity of these neurons. Three important new aspects of TAs action have recently emerged: (a) inhibition of firing due to increased release of dopamine; (b) reduction of D2 and GABAB receptor-mediated inhibitory responses (excitatory effects due to dysinhibition); and (c) a direct TA1 receptor-mediated activation of GIRK channels which produce cell membrane hyperpolarization. While the first two effects have been well documented in our laboratory, the direct activation of GIRK channels by TA1 receptors has been reported by others, but has not been seen in our laboratory (Geracitano et al., 2004). Further research is needed to address this point, and to further characterise the mech